Education, anthropology, ontologies (Educação e Pesquisa, 2016)
The goal of this paper is to analyze the relation between anthropology and education, and the relation of both with the experience of life, in a context of debates in which epistemological concerns have gradually been substituted by a reflection on the ontological dimension of existence. Starting with a discussion on the asymmetric historical relation between anthropology and education, in what concerns the analysis of sociocultural dimensions of learning, we propose the inversion of terms of the expression anthropology of education, and then discuss the paradoxes that characterize the relation between the professional education of the anthropologist, identified as an epistemological exercise, and the ontological dimension of the ethnographic experience. From this discussion, the question of the body of the ethnographer emerges as something absent in mainstream ethnographic production, which is identified as an index of the presence of one of the structuring dichotomies of Western epistemology: the separation of mind and body. The works of authors associated to the so-called ontological turn in social sciences are brought to the discussion, and from the analysis of some of their main contributions, new points of contact between education and anthropology, on more symmetric grounds, emerge. From these, it is of special interest the one that focuses on happiness and the plenitude of becomings, which, albeit an unprecedented theme in anthropology, has been part of the pedagogical debates of the last four decades.